PENGARUH ORIENTASI PASAR UNTUK MENINGKATKAN KINERJA PEMASARAN MELALUI KEUNGGULAN BERSAING SEBAGAI VARIABEL MEDIASI PADA PELAKU USAHA INDUSTRI RUMAH PANGGUNG DI KECAMATAN WOLOAN KOTA TOMOHON - Raintung, Michael Ch.; Kawet, Raymond Ch.; Lumatow, Rudie Y. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstract: This study aims to determine the influence of market orientation on improving marketing performance through competitive advantage as an intervening variable in stilt house industry business actors in Woloan Village, Tomohon City. The population in this study is 61 stilt house entrepreneurs, the sampling technique uses a saturated sampling technique where all members of the population are sampled, namely 61 respondents. The data collection technique uses data with questionnaires. The instrument testing in this study was carried out based on validity test and reliability test, and analyzed using path analysis. The results of the study show that market orientation partially has a positive and significant effect on competitive advantage. Competitive advantage partially has a positive and significant effect on marketing performance, market orientation partially has a positive and significant effect on marketing performance, and the results of the indirect influence of market orientation through competitive advantage on marketing performance are obtained as proof that competitive advantage can mediate The relationship between market orientation and marketing performance Keywords: Market orientation, competitive advantage, marketing performance. house on stilts. Abstract: This study aims to determine the influence of market orientation on improving marketing performance through competitive advantage as an intervening variable in stilt house industry business actors in Woloan Village, Tomohon City. The population in this study is 61 stilt house entrepreneurs, the sampling technique uses a saturated sampling technique where all members of the population are sampled, namely 61 respondents. The data collection technique uses data with questionnaires. The instrument testing in this study was carried out based on validity test and reliability test, and analyzed using path analysis. The results of the study show that market orientation partially has a positive and significant effect on competitive advantage. Competitive advantage partially has a positive and significant effect on marketing performance, market orientation partially has a positive and significant effect on marketing performance, and the results of the indirect influence of market orientation through competitive advantage on marketing performance are obtained as proof that competitive advantage can mediate The relationship between market orientation and marketing performance Keywords: Market orientation, competitive advantage, marketing performance. house on stilts.